How to Integrate ESG into Investment Decision‐Making: Results of a Global Survey of Institutional Investors. Issue 4 (20th February 2018) - Eccles, Robert G.; Kastrapeli, Mirtha D.; Potter, Stephanie J.
Abstract : The authors review the findings of their global survey of 582 institutional investors that were either practicing or planning to practice some degree of integration of environmental, social, and governance (ESG) factors into their investment decision‐making process. The investors were evenly split between asset owners and asset managers, equity and fixed income, and across the three regions of the Americas, Asia Pacific, Europe, Middle East, and Africa. The survey explored reasons for ESG investing; the barriers to such investing and investor approaches to overcoming them; and the time frames used for making investment decisions, evaluating the performance of managers, and awarding compensation. The authors report finding that the commonly perceived barriers to ESG integration—the belief that ESG integration requires sacrificing returns, that fiduciary duty prevents one from doing so, and unrealistically short‐term expectations for ESG to deliver outperformance—were not as great as commonly believed. The biggest barrier is the lack of high quality data about the performance of companies on their material ESG factors—a scarcity that the authors attribute to the lack of standards for measuring ESG performance and the lack of ESG performance data reported by companies. The results were very similar between asset owners and asset managers, equity and fixed income, and across regions. However, the investment horizons of asset owners were notably longer than those of asset managers, and the same was true of equity vs. fixed income investors. Investors in the Americas were more patient about time frames for seeing outperformance from ESG, while those in Asia Pacific were the least patient. There were also differences across regions in how to overcome the barriers to ESG integration.